Mapping the human brainstem: Brain nuclei and fiber tracts at 3 T and 7 T. (9th July 2019) - Straub, Sina; Knowles, Benjamin R.; Flassbeck, Sebastian; Steiger, Ruth; Ladd, Mark E.; Gizewski, Elke R.
Abstract : Structural high‐resolution imaging of the brainstem can be of high importance in clinical practice. However, ultra‐high field magnetic resonance imaging (MRI) is still restricted in use due to limited availability. Therefore, quantitative MRI techniques (quantitative susceptibility mapping [QSM], relaxation measurements [ R 2 *, R 1 ], diffusion tensor imaging [DTI]) and T 2 ‐ and proton density (PD)‐weighted imaging in the human brainstem at 3 T and 7 T are compared. Five healthy volunteers (mean age: 21.5 ± 1.9 years) were measured at 3 T and 7 T using multi‐echo gradient echo sequences for susceptibility mapping and R 2 * relaxometry, magnetization‐prepared 2 rapid acquisition gradient echo sequences for R 1 relaxometry, turbo‐spin echo sequences for PD‐ and T 2 ‐weighted imaging and readout‐segmented echo planar sequences for DTI. Susceptibility maps were computed using Laplacian‐based phase unwrapping, V‐SHARP for background field removal and the streaking artifact reduction for QSM algorithm for dipole inversion. Contrast‐to‐noise ratios (CNRs) were determined at 3 T and 7 T in ten volumes of interest (VOIs). Data acquired at 7 T showed higher CNR. However, in four VOIs, lower CNR was observed for R 2 * at 7 T. QSM was shown to be the contrast with which the highest number of structures could be identified. The depiction of very fine tracts such as the medial longitudinal fasciculus throughout the brainstem was only possible in susceptibility maps acquired at 7 T. DTI effectively showed the main tracts (crus cerebri, transverse pontine fibers, corticospinal tract, middle and superior cerebellar peduncle, pontocerebellar tract, and pyramid) at both field strengths. Assessing the brainstem with quantitative MRI methods such as QSM, R 2 *, as well as PD‐ and T 2 ‐weighted imaging with great detail, is also possible at 3 T, especially when using susceptibility mapping calculated from a gradient echo sequence with a wide range of echo times from 10.5 to 52.5 ms. However, tracing smallest structures strongly benefits from imaging at ultra‐high field. Abstract : Ultra‐high field magnetic resonance imaging is still restricted in use. Therefore, quantitative susceptibility and R 2 * mapping, R 1 mapping, diffusion tensor imaging, and T 2 ‐ as well as proton density‐weighted imaging in the human brainstem at 3 T and 7 T, are compared. Great detail can be obtained already at 3 T when assessing the brainstem with these methods, especially with susceptibility mapping. However, tracing smallest structures strongly benefits from the use of an ultra‐high field.